Acyclovir-induced Acute Kidney Injury Resolved After Switching to Famciclovir (Revista de Medicina Clinica, 2025)
The herpes simplex virus type 2 (HSV-2) is a common pathogen that typically presents asymptomatically or causes mild mucocutaneous infections. Following primary infection, it establishes latency in the ganglia and can later reactivate, leading to severe infections at other sites, such as the central nervous system (CNS). These infections are treated with acyclovir, a DNA polymerase inhibitor that, in its intravenous form, achieves adequate cerebrospinal fluid (CSF) concentrations. However, it may cause neurotoxicity and nephrotoxicity. We present a case of HSV-2 meningitis in a patient who developed neurotoxicity and nephrotoxicity due to acyclovir. Both resolved after switching to famciclovir, highlighting the need for further studies to assess the safety and efficacy of this antiviral in this context.
Keywords: Acyclovir; Famciclovir; Nephrotoxicity; Meningitis; HSV2